A Study on Biofilm Formation in Relation to Oral Hygiene Status Related to Tooth Brushing Practice - Akbar, Tamanna; Hasan, Hasibul; Awal, Md Abdul; Ghosh, Milon Kumar; Haque, Md Jawadul; Sultana, Nihar (Update Dental College Journal, 2017)
Introduction:The aim of the present study was to assess the biofilm formation in oral cavity and its relationship with oral hygiene status related to practice of tooth brushing among school going children in Rajshahi, Bangladesh. Materials and methods: A descriptive cross-sectional study was carried out among the 386 school going children with age range of 6-16 years old. The study was carried out in the police line school, Rajshahi. Data were collected through a semi-structured questionnaire and analyzedby using SPSS software version 21.0. Result: The most prevalent age group of the study was 6-11 years with frequency 192(49.7%).The proportion of the boys and girls was1.71: 1. It was found that 243(66.8%) students learnt about tooth brushing from their family and235(60.9%) of total studentsbrush their tooth once in a day. Majority367(95.1%) of them use tooth paste as dentifrices and377(97.7%) use tooth brush as tooth brushing instrument. Only 2(0.5%)studentsdo not brush their teeth at all. We also found, that mostof them 274(71%) used horizontal tooth brushing technique. This study showed the relationship between practice of tooth brushing of the respondents and the index of biofilm formationthat was statistically insignificant (p> 0.05), but relationship between respondents oral hygiene status and biofilm formation is statistically significant (p< 0.05). Conclusion: It was assessing that state of oral hygiene condition of school going children can be improved by prevention of biofilm formation, and also suggesting to ensure the practice of regular brushing of teeth. Update Dent. Coll. j: 2017; 7 (1): 21-25